2000
DOI: 10.1359/jbmr.2000.15.9.1683
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Expression of Novel Genes During Osteoblast Differentiation

Abstract: To achieve new insights into the coordinate regulation of gene expression during osteoblast differentiation we utilized an approach involving global analysis of gene expression to obtain the identities of messenger RNAs (mRNAs) expressed using an established in vitro model of bone development. MC3T3-E1 osteoblast-like cells were induced to differentiate by the addition of ␤-glycerophosphate (␤-GP) and ascorbic acid. RNA samples derived from induced and uninduced control MC3T3-E1 cells were used to prepare comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 79 publications
3
35
0
Order By: Relevance
“…Furthermore, the expression of S100 in osteoblastic cells was verified in various types of osteosarcomas, in which immunohistochemical staining for S100 was used to analyze the proliferating cells in osteosarcomas, and the main proliferating cells to be stained were found to be mature osteoblast-like cells (27,28). The existence of the S100 family in osteoblasts were confirmed in subsequent studies (18,29). S100 family members share a common S100 calcium-binding motif and have several regulatory functions in, not only protein phosphorylation, some enzyme activities, the dynamics of cytoskeletal components, transcription factors, and Ca 2ϩ homeostasis but also the cell proliferation and differentiation (15,16).…”
Section: The Effects Of Transient Transfection Of Pcdna-cacy Plasmid mentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the expression of S100 in osteoblastic cells was verified in various types of osteosarcomas, in which immunohistochemical staining for S100 was used to analyze the proliferating cells in osteosarcomas, and the main proliferating cells to be stained were found to be mature osteoblast-like cells (27,28). The existence of the S100 family in osteoblasts were confirmed in subsequent studies (18,29). S100 family members share a common S100 calcium-binding motif and have several regulatory functions in, not only protein phosphorylation, some enzyme activities, the dynamics of cytoskeletal components, transcription factors, and Ca 2ϩ homeostasis but also the cell proliferation and differentiation (15,16).…”
Section: The Effects Of Transient Transfection Of Pcdna-cacy Plasmid mentioning
confidence: 84%
“…An interesting feature of the S100 proteins is that they are expressed by epithelial cells and fibroblasts in a cell-specific way (17). Calcyclin is also expressed by osteoblasts (MC3T3-E1 cells) and up-regulated markedly during osteoblast differentiation; however, its roles in bone physiology are unknown (18).…”
mentioning
confidence: 99%
“…This result is interesting because MEF is proven to be decreased during osteogenic differentiation, (11) whereas Ets2 is expressed at high levels during the differentiation and matrix maturation phase in the MC3T3-E1 model of osteoblast development. (18) If Ets2 is an important player in the osteoblast differentiation and matrix maturation phase, transgenic mice overexpressing Ets2 are expected to have increased bone mass. However, our MEF TG mouse showed osteopenia, and our previous data also showed that MEF has an inhibitory role in osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This process of differentiation has been subdivided into three developmental stages: proliferation, extracellular matrix synthesis and maturation, and mineralization, each of which as characteristic changes in gene expression (8). Many independent studies of patterns of gene expression during osteoblast differentiation have been reported (9)(10)(11), and those studies found that some apolipoproteins were induced during this process (9).…”
Section: Introductionmentioning
confidence: 99%